Export assistance: A literature review and challenges for future research - Flávia Holanda de Schmidt; Jorge Ferreira da Silva (Institute for Applied Economic Research (ipea), 2015)
Strengthening commitments for export assistance and establishing comprehensive programs to expand export activities of firms are part of the public policies in almost all developed and developing countries. Not only have governments increased the amounts devoted to these actions in recent decades, but the number of support agencies for export has tripled in the context of developing national strategies for global exports. Despite the fact that contributions on the subject have been on the agenda of many authors for over thirty years, conceptual and ethodological disagreement persists as to the effects and impacts of the adoption of export programs on the performance of the recipient firms. Considering (i) that government resources are scarce and require a major effort for optimal allocative efficiency, and (ii) that, as such, public policies must be strongly grounded on the evidence, a significant body of empirical studies devoted to the understanding of export support has recently been developed in the area of International Business. The aim of this paper is to assess the current status of issues related to the promotion of exports and to develop a deeper understanding of the phenomenon, based on a survey of the empirical studies on the subject published between 1992 and 2011. All 25 identified articles were coded according to the same method of analysis, based on objective criteria. The analysis indicates that the production has evolved between the two subperiods surveyed, both in quantity and quality, and evidences an evolution over the period analyzed, especially in relation to the diversification of the loci of research, the adoption of more robust statistical techniques, and the advent of longitudinal studies. Certain limitations, however, were still observed, even in more recent studies, and in these cases, several recommendations for researchers are made.
Keywords: F23; M16; M38; 330; internationalization; export assistance; export performance